Pre-clinical Studies Identifying Molecular Pathways of Neuroinflammation in Parkinson's Disease: A Systematic Review - Fathi, Mobina; Vakili, Kimia; Yaghoobpoor, Shirin; Qadirifard, Mohammad Sadegh; Kosari, Mohammadreza; Naghsh, Navid; Asgari taei, Afsaneh; Klegeris, Andis; Dehghani, Mina; Bahrami, Ashkan; Taheri, Hamed; Mohamadkhani, Ashraf; et al. (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD), the second most common neurodegenerative disorder, is characterized by neuroinflammation, formation of Lewy bodies, and progressive loss of dopaminergic neurons in the substantia nigra of the brain. In this review, we summarize evidence obtained by animal studies demonstrating neuroinflammation as one of the central pathogenetic mechanisms of PD. We also focus on the protein factors that initiate the development of PD and other neurodegenerative diseases. Our targeted literature search identified 40 preclinical in vivo and in vitro studies written in English. Nuclear factor kappa B (NF-kB) pathway is demonstrated as a common mechanism engaged by neurotoxins such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 6-hydroxydopamine (6-OHDA), as well as the bacterial lipopolysaccharide (LPS). The α-synuclein protein, which plays a prominent role in PD neuropathology, may also contribute to neuroinflammation by activating mast cells. Meanwhile, 6-OHDA models of PD identify microsomal prostaglandin E synthase-1 (mPGES-1) as one of the contributors to neuroinflammatory processes in this model. Immune responses are used by the central nervous system to fight and remove pathogens; however, hyperactivated and prolonged immune responses can lead to a harmful neuroinflammatory state, which is one of the key mechanisms in the pathogenesis of PD.